2013
DOI: 10.1111/ics.12054
|View full text |Cite
|
Sign up to set email alerts
|

Towards an insight on photodamage in hair fibre byUV‐light: An experimental and theoretical study

Abstract: The biochemistry concerning these reactions is essentially important for a biological system where the degradation of Trp occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…Previous studies of the fluorescence characteristics of the hair suggested that the fluorescence from the tryptophane contributed significantly to the 340 nm band as a correlation was observed between the fluorescence intensity of that band and the number of tryptophanes in UV-damaged hair [12]. What makes the dose response curve steeper at the low UV-radiation doses, is the sufficient number of intact tryptophans per the targeting surface of hair.…”
Section: Figure 5 Changes In Content Of Sh-groups Of Human Hair Expomentioning
confidence: 96%
“…Previous studies of the fluorescence characteristics of the hair suggested that the fluorescence from the tryptophane contributed significantly to the 340 nm band as a correlation was observed between the fluorescence intensity of that band and the number of tryptophanes in UV-damaged hair [12]. What makes the dose response curve steeper at the low UV-radiation doses, is the sufficient number of intact tryptophans per the targeting surface of hair.…”
Section: Figure 5 Changes In Content Of Sh-groups Of Human Hair Expomentioning
confidence: 96%
“…UV irradiation induced hair damage is called photodamage. UV irradiation weakens the structural integrity of hair fiber, resulting in the degradation of amino acids 5 , oxidation of internal lipid 6 and melanin granules 7 . Cystine is photo-oxidized into sulfo alanine, which is regarded as an important indicator of the decomposition of hair fiber and in turn affects the mechanical properties of hair fiber 8 .…”
mentioning
confidence: 99%
“…When it is desired to evaluate the effects of solar radiation on the degradation of the internal structures of hair [39][40][41][42] or also hair photo-protection obtained by cosmetic ingredients [40][41][42][43], photoluminescence spectroscopy analysis can be used, because in hair amino acids susceptible to photo-degradation such as tryptophan (Trp), an intrinsic fluorophore is present. Disulphide bonds in keratin, where significant losses in Trp, prior to any increase in photo-oxidation products, are detected [42].…”
Section: Photoluminescence Spectroscopymentioning
confidence: 99%
“…Protein loss [11,12,[44][45][46][47][48]; Electrophoresis [13,25]; Scanning Electron Microscopy [5,[19][20][21][22]; Transmission Electron Microscopy [6,24,25]; Atomic Force Microscopy [7,26,[28][29][30][31]; Optical Coherence Tomography [8,33]; RAMAN spectroscopy [10,[32][33][34] Hair Shine-Gloss Diffuse reflectance spectrophotometry [14,33,43,46,50] Easy to comb Combing resistance [12,64,65] Strength properties Resistance to breakage [12,14,16,33,61,62] Photoprotection Photoluminescence spectroscopy [40][41][42][43] Long-lasting color Diffuse reflectance spectrophotometry [14,…”
Section: Damage Hair Reductionmentioning
confidence: 99%